2008
DOI: 10.1016/j.ecss.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of HPLC–CHEMTAX analysis for determining phytoplankton biomass and composition in a turbid estuary (Schelde, Belgium)

Abstract: In the upper Schelde estuary in 2002, phytoplankton biomass and community composition were studied using microscopic and pigment analyses. Chlorophyll a concentration was a good predictor of phytoplankton biomass estimated from cell counts and biovolume measurements. The phytoplankton carbon to chlorophyll a ratio, however, was often unrealistically low (<10). CHEMTAX was used to estimate the contribution of the major algal groups to total chlorophyll a. The dominant algal groups were diatoms and chlorophytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…Cultivated AAP bacteria modulate the BChl a quota as much as 10-fold in response to light availability (Koblízek et al, 2003;Li et al, 2006), similar to photoadaptation by phytoplankton. As a result of photoadaptation, phytoplankton C-to-chlorophyll a ratios are low in turbid estuaries, such as the Schelde (Lionard et al, 2008), and high in clearer oceanic environments, such as the subtropical Atlantic Ocean (Veldhuis and Kraay, 2004). In contrast, the BChl a quota of AAP bacteria in Chesapeake Bay was not higher than that in the coastal North Atlantic Ocean and in the South Pacific Ocean.…”
Section: Discussionmentioning
confidence: 81%
“…Cultivated AAP bacteria modulate the BChl a quota as much as 10-fold in response to light availability (Koblízek et al, 2003;Li et al, 2006), similar to photoadaptation by phytoplankton. As a result of photoadaptation, phytoplankton C-to-chlorophyll a ratios are low in turbid estuaries, such as the Schelde (Lionard et al, 2008), and high in clearer oceanic environments, such as the subtropical Atlantic Ocean (Veldhuis and Kraay, 2004). In contrast, the BChl a quota of AAP bacteria in Chesapeake Bay was not higher than that in the coastal North Atlantic Ocean and in the South Pacific Ocean.…”
Section: Discussionmentioning
confidence: 81%
“…In studies of different habitats, including an estuary (Lionard et al 2008), a bay (Madhu et al 2014), lagoons (Sarmento & Descy 2008), and freshwater (Guisande et al 2008), many adjustments were made to the choice of pigment matrix and the initial ratio. The intent was to isolate and incubate the phytoplankton in the laboratory to discover the pigment/Chl a ratio, but finding the ratio for every phylum was complex.…”
Section: Chemtax Analysis Of Pigment Datamentioning
confidence: 99%
“…5a) in the freshwater estuary (between km 120 and 80) could be explained by the use of an inappropriate C:Chl a ratio for freshwater phytoplankton. Indeed, C:Chl a ratio measured in the Scheldt estuary highly varies with values between 1 and 70 (Lionard et al, 2008b). Sensitivity tests suggest that the model-data fit can be improved by modifying the C:Chl a ratio (not shown).…”
Section: Annual Estuarine Profiles Of Biogeochemical Variablesmentioning
confidence: 99%
“…8b,d), with the Chlorophyceae contributing significantly (>50%) to phytoplankton in summer between km 140 and 160. On an annual mean basis, other algal groups represent less than 10% (Lionard et al, 2008b) and simulated cyanobacteria (not shown) represent a negligible biomass (b 2 mgC m −3 ). As observed (Lionard et al, 2008a,b), freshwater phytoplankton is present from spring to early autumn.…”
Section: Seasonal Biogeochemical Trends Along the Estuarymentioning
confidence: 99%